Understanding racism and sexism in Harry Potter and Stuart Hall's model of three reading positions - Orel, Brigita (ELOPE (Ljubljana), 2007)
In the Harry Potter book series there are several examples of sexist and racist stereotypes which can distort children's understanding of reality and thus cause them to adopt prejudices and inappropriate judgments. The reason for such strong impact on the young readers can be explained with the use of Stuart Hall's encoding/decoding model that suggests three reading positions and, as a result, three different ways of understanding one and the same text. The fact that oppositional reading, which allows the reader to asses the text critically, can only be adopted by educated and well-read readers explains why adult help is needed in directing the child reader towards a correct interpretation of such deficiencies of a text and offering a grounded explanation.
Keywords: angleška književnost; Hallov model vrst branja; otroci; otroška književnost; rasizem; seksizem; stereotipi